Análise e caracterização da potência elétrica gerada com elemento piezoelétrico - Moreira Filho, Robério Paredes (2014)
This work presents a characterization study of a piezoelectric element for generating electricity. This characterization allowed the determination of the relationship between mechanical deformation experienced by the element generator (piezoelectric) and the electric power generated. The results of the study were based on simulations using a finite element program (ANSYS) and experimental data. Was used the ceramic Lead Zirconate Titanate (PZT) as the piezoelectric element of the generator. We developed a generator comprised of a basic cantilever beam excited by a shaker (exciter) at the frequencies of interest. With the use of this generator, it was established that the maximum voltage generation and electrical power occurred at a frequency of 75 Hz. For a load of 19.69 kΩ, which divided the voltage generated under no load condition by half at the frequency of 75 Hz, it was provided an electric power of 1,877 mW for a deformation of 387,97 μm/m on the PZT. For this frequency, the results of elastic deformation and voltage in the simulations, showed to be equivalent to those achieved in the experiment.